Application of the Inquiry Learning Model to Improve Student English Learning Achievement - Purwo Haryono (Sustainable, 2023)
In learning English, teachers use many learning models in the classroom, one of which is inquiry. The inquiry model is a model used in the teaching and learning process where students can ask, examine, or investigate a problem, involving all students. the ability to search and investigate systematically, critically, logically and analytically so that students can formulate in their own way. This research aims to determine the effect of Inquiry model cooperative learning on students' English learning outcomes. The research method used is a qualitative method. The research results are in the form of an English language learning process by applying the Inquiry learning model and English language learning outcomes values are collected using observation, interview and documentation techniques. Research data was analyzed using a descriptive approach. The research results stated that in cycle I the students' English learning outcomes were 80% (good), and in process II it increased to 87.7% (good). Thus, it can be concluded that the application of the Inquiry learning model can improve students' English learning achievement.